Factors associated with inpatient complications among patients with obesity and COVID‐19 at an urban safety‐net hospital: A retrospective cohort study - Tyler J. Ryan; Annie S. Heyman; Elizabeth N. Mulvey; Angela McLaughlin; Ivania M. Rizo; Sabrina A. Assoumou (Wiley, 2022)
Abstract Objective Obesity increases morbidity and mortality from Coronavirus disease 2019 (COVID‐19). This study characterized inpatient complications among patients with obesity and COVID‐19-including myocardial infarction, renal failure requiring dialysis, stroke, secondary bacterial infection, and venous thromboembolism-and identified factors associated with developing at least one inpatient complication at a safety‐net hospital with a diverse cohort. Methods A retrospective review was performed of all patients admitted for ≥3 days with COVID‐19 between 16 March 2020, and 8 April 2020. Logistic regression identified factors associated with developing at least one COVID‐19‐related complication among patients with obesity (body mass index ≥30 kg/m2). Results 374 patients were included; 53.7% were classified as having obesity, 43.9% identified as Black, and 38.5% identified as Latino or Hispanic. Obesity was not associated with having at least one inpatient complication on multivariable analysis, but increased age (aOR 1.02, [95% CI 1.01-1.04], p = 0.010) and obstructive sleep apnea (aOR 2.25, [1.08-4.85], p = 0.034) were associated with this outcome. Conclusions Obesity was not associated with specified inpatient complications among patients with COVID‐19 admitted to a health system caring for diverse patients. Future studies should incorporate larger cohorts and reflect newer treatment protocols.